Vicissitudes and prospects of green roof research: a two-decade systematic bibliometric review - Xie, Chunping; Liu, Dawei; Jim, C. Y. (Frontiers in Ecology and Evolution, 2024)
Urban green roofs have emerged as an innovative nature-based solution for enhancing urban sustainability and resilience. Based on the Web of Science Core Collection database, the scholarly papers on green roofs published in the past two decades were analyzed quantitatively and visualized using bibliometric techniques. The study scope covered research countries, institutions, main journals, crucial authors, highly cited documents, hot topics, and research frontiers. The 3210 publications mined from the bibliographic database on green roofs have increased progressively in the study period, with a significantly faster pace in recent years. The research subjects changed gradually over time, extending into more disciplines and becoming decidedly multidisciplinary. The notable bibliometric features registered a pronounced spatial concentration of research outputs in a small number of countries, regions, research institutions, journals, and researchers, mainly associated with developed metropolises. The number of publications and citation impacts identified the world's top ten researchers and journals. Well-defined clusters depicted by knowledge graphs indicated a diverse range in the number and strength of inter-node connections for countries, institutions, researchers, and research topics defined by keywords. The research scope focuses on quantifying benefits and costs and optimizing designs to maximize biodiversity, hydrologic, thermal, and energy benefits as urban sustainability and climateadaptation solutions. Emerging research should enhance biodiversity through optimal plant selection, integrate green roofs with renewable energy systems for sustainability, apply computational tools to enhance designs, evaluate low-cost and locally relevant design options for developing cities, and quantify co-benefits like stormwater reduction and energy savings. Multidisciplinary efforts leveraging simulations, ecosystem services valuation, and participatory community partnerships can advance context-appropriate green roof innovation and evidence-based policymaking to expand adoption in cities worldwide. Quantifying and communicating co-benefits are critical measures to drive wider implementation.